PRZESTRZEŃ MIEJSKA – DZIELENIE POSTRZEGALNEGO. PRÓBA ANALIZY PROCESÓW ZAWŁASZCZANIA PRZESTRZENI MIEJSKIEJ Z PERSPEKTYWY FILOZOFII JACQUESA RANCIÈRE’A - Podgórski, Michał (Pracowania Humanistycznych Studiów Interdyscyplinarnych WFPiK UAM, 2011)
The article is an attempt at showing the implementation of Jacques Ranciere’s theory in contemplating about city space, its division, appropriation and privatization. The first part of paper is focused on presentation of approaches describing processes of appropriation of space, which are dominant on the sociological field. There are two main interpretations: (1) first perspective reduces appropriation to legal or factual annexation of space, authors write here about gentrification, gated communities or privatization of public space by corporations; (2) second perspective reduces appropriation to visual (over)presence, of which the best example is ostentatious presence of billboards in public place and appropriation/retrieval of space with such activities as painting graffiti and sticking stickers. Unfortunately, these two perspectives do not include the wholeness of processes of appropriation which take place in the city, because of two reasons: (1) these two perspectives unwillingly relate to the fact that city is aesthetic space (city continually provides innumerable volume of aesthetic experiences); (2) both perspectives completely ignore the fact that city is »multi-sensual world« (city provides not only visual experiences but it is full of sounds, scents and kinaesthetic experiences). So, there is requirement of using multi-sensual perspective to make the recognition about processes of appropriation of city space more complex. The next part of article is devoted to presentation of Ranciere’s conception of the distribution of the sensible, as the one of possible strategies of analyzing processes of appropriation of city space in terms of aesthetic experiences. The distribution of the sensible is sensuously accessible system of relations between objects which is connected with specified time and space, in other words: this system defines what can be seen and heard at given moment in such place. Therefore, the distribution of sensible defines where each element/individual should be »placed«, with whom each individual can talk, which language is appropriate in specified space-time, and, finally, which scents are proper there. Processes of distribution of the sensible will be discuss on example of changes of historical centers of polish cities which took place after the 1989.
Keywords: estetyka; estetics; zmysły; senses; miasto; city; podział; division; fragmentacja; fragmentation; zawłaszczanie; appropiation